Financial inclusion of the informal sector of marginalized counties in Kenya - Richard Wamalwa Wanzala; Lawrence Ogechukwu Obokoh (Cogent Social Sciences, 2025)
This study investigates financial inclusion among informal sector participants in five marginalized Kenyan counties, Samburu, Narok, Turkana, Garissa, and West Pokot, where inclusion rates fall below 70%. Drawing on data from the 2024 FinAccess Household Survey, the researchers selected a purposive sample of 320 respondents and analyzed it using a probit model to identify key determinants of financial inclusion. The results indicate that financial inclusion remains persistently low due to income instability, geographic isolation, and weak financial infrastructure. However, formal business registration, financial literacy, and the use of digital financial services enhance inclusion. Gender, education level, and business turnover correlate positively with inclusion, while marital status and age show negative associations. Notably, internet access, mobile agent networks, and digital loans appear to reduce financial inclusion, whereas mobile money usage contributes positively. Formal financial services yield mixed outcomes: while bank account ownership and SACCO participation negatively affect inclusion, access to credit, savings accounts, microfinance institutions, and financial advisory services positively influence it. These findings highlight the need for targeted, context-specific policies that address both structural and digital barriers to financial access. Strengthening financial inclusion in these regions will support poverty reduction and advance Kenya’s progress toward the Sustainable Development Goals.